Kombinasi Dosis Pakan Terhadap Pertumbuhan Udang Windu (Penaeus monodon) - Dian Lestari; Suci Anggriani; Tenriware Tenriware; Reski Fitriah; Nur Indah Sari Arbit; Fauzia Nur; Chairul Rusyd Mahfud (Departemen Akuakultur FPIK UNDIP, 2023)
The success of the tiger prawn seeding business is the first step in the cultivation chain system that will support the business of providing quality seeds. One of the factors that really determines the quality of shrimp seeds is the quality and quantity of feed. This study aims to determine the appropriate dose ratio of natural feed and artificial feed for the growth of tiger prawns in the post larval stage. This research was conducted in September 2020. This study used a Completely Randomized Design (CRD) which consisted of 3 treatments 20 artemia/larvae, 25 artemia/larvae, 30 artemia/larvae. Each treatment was repeated three times. Parameters tested included absolute weight growth, absolute body length, feed efficiency, survival rate, and water quality. Data analysis used ANOVA to see the significance of the effect on the growth of absolute body weight, absolute body length, feed efficiency, survival rate and water quality were analyzed descriptively. The highest average absolute weight growth was obtained in treatment C (0.8 gram) then treatment B (0.65 gram) and the lowest was in treatment A (0.62 gram). The highest mean absolute body length was obtained in treatment C (6.6 mm), then B (5.4 mm) and the lowest was in treatment A (4.3 mm). The highest average value of feed efficiency was in treatment C (9.25%) followed by treatment B (7.56%) and the lowest in A (7.17%). The highest average survival value of tiger shrimp post larvae was obtained in treatment C (77%), followed by treatment B (67%) and the lowest in treatment A (19%). In general, the dose of artemia 30 heads/post larvae was the best treatment with an average weight (0.8 gram), body length (6.6 mm), feed efficiency (9.25%) and survival rate (77%).Keywords: artemia, survival rate, growth, tiger shrimp